2019
DOI: 10.24875/bmhim.m18000020
|View full text |Cite
|
Sign up to set email alerts
|

Fiebre y terapia antipirética en el paciente con sepsis en la unidad de cuidados intensivos: actualización

Abstract: Fever is a very common sign to observe in critically ill children during their intensive care unit stay. This should be understood as an evolutionary biological response, of normal adaptive character, from the host to the physiological stress. It is the result of a complex response to pyrogenic stimuli, resulting in the generation of cytokines and prostaglandins. The molecular mechanisms involved in the onset of fever are not yet fully specified, thus creating difficulties in the knowledge of the exact pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 118 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Lack of fever and leukocytosis led to increased mortality in community acquired pneumonia in the elderly, and another study has demonstrated that introducing acetaminophen, the common drug for fever, did not help reduce the intensive care unit admission days in the elderly with infection 20,21 . On the other hand, there is evidence showing the benefit of reducing fever, such as averting febrile convulsion in children, which may result in brain injuries and neuropsychiatric alterations 22,23 and also in the elderly where the extra metabolic cost and the danger of organic damage from fever exists due to debilitating co-morbidities 22,24,25 . Thus, while there is logic behind suppressing fever as it can be detrimental, it is not entirely clear in what way the presence of fever is beneficial or in which situation harmful to the body 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Lack of fever and leukocytosis led to increased mortality in community acquired pneumonia in the elderly, and another study has demonstrated that introducing acetaminophen, the common drug for fever, did not help reduce the intensive care unit admission days in the elderly with infection 20,21 . On the other hand, there is evidence showing the benefit of reducing fever, such as averting febrile convulsion in children, which may result in brain injuries and neuropsychiatric alterations 22,23 and also in the elderly where the extra metabolic cost and the danger of organic damage from fever exists due to debilitating co-morbidities 22,24,25 . Thus, while there is logic behind suppressing fever as it can be detrimental, it is not entirely clear in what way the presence of fever is beneficial or in which situation harmful to the body 26,27 .…”
Section: Introductionmentioning
confidence: 99%